Clinical research Reference curves of anthropometric indices and serum lipid profiles in representative samples of Asian and European children - Kelishadi, Roya; Schwandt, Peter; Haas, Gerda-Maria; Hosseini, Mohsen; Mirmoghtadaee, Parisa (Archives of Medical Science, 2008)
Introduction: To compare the reference curves and mean values of anthropometric indices and lipid profiles of a population-based sample of Asian and European children. Material and methods: The data of 2076 Iranian and 1721 German children, aged 6-11 years, were compared. For anthropometric indices, we considered weight, height, body mass index (BMI), waist circumference (WC), hip circumference and waist-to-hip ratio. Fasting serum lipid profile including triglycerides, total, LDL and HDL cholesterol, and total cholesterol/HDL ratio were compared between the two populations studied. Smoothed age-specific percentiles for anthropometric indices and serum lipid profile were constructed by using the software package LMS Chart Maker. Results: The mean of anthropometric indices was higher in Iranian than in German children. The mean triglycerides (TG) and total/HDL cholesterol ratio were higher, and the mean total, LDL and HDL cholesterol were lower in Iranian than in German children. The reference curves for BMI and WC were higher and had a sharper increase in Iranian than in German children. The reference curves of TG were higher, and those of total and HDL cholesterol were lower, in Iranian than in German children, whereas LDL cholesterol curves had no significant difference. Conclusions: Reference curves and cut-off values should be provided for anthropometric indices and lipid profile of children with different ethnicities. Differences in lipid profiles in various populations, and the higher values of the components of the metabolic syndrome (high WC and TG as well as low HDL-C) in young Asian children, should be considered in the current guidelines for screening lipid disorders in the paediatric age group.